Effects of supplemental carbohydrate ingestion during superimposed electromyostimulation exercise in elite weightlifters - Wax, B.; Kavazis, A. N.; Brown, S. P. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this investigation was to test the effects of carbohydrate supplementation on blood parameters and force output during superimposed electromyostimulation (SEMS) single-leg isometric contractions. We hypothesized that carbohydrate ingestion before and during muscle contractions would lead to greater glucose availability and greater total force output for the session. Six elite resistance trained male subjects participated in a randomized, counterbalanced, double-blind study. The subjects were randomly assigned to placebo (PL) or carbohydrate (CHO). The subjects in CHO consumed 1 g of carbohydrate per kilogram of body mass loading dose and 0.17 g of carbohydrate·per kilogram of body mass every 6 minutes during the exercise protocol. The PL received an equal volume of a solution made of saccharin and aspartame. The exercise protocol consisted of repeated 20-second isometric contractions of quadriceps muscle at 50% maximal voluntary contraction followed by 40 seconds of rest until failure occurred. Importantly, quadriceps maximal voluntary contraction with SEMS was performed in the beginning and then every 5 minutes during the last 3 seconds of isometric contractions throughout the exercise protocol. Venous blood samples were taken preexercise, immediately postexercise, and at 5 minutes postexercise and analyzed for glucose, nonesterified fatty acids, and glycerol. Our results indicate that CHO ingestion increased (p < 0.05) plasma glucose, but no significant differences (p > 0.05) were detected for nonesterified fatty acids or glycerol. Importantly, total force output during exercise protocol was higher (p < 0.05) in CHO compared with that in PL. Therefore, our data suggest that CHO supplementation before and during exercise may be beneficial for individuals performing high-volume resistance training.